Longevity and statistical modelling - Yang, Bowen (2017)
This dissertation consists of two studies on the modelling aspects of mortality (or longevity). In the first paper, we examine cohort extensions of the Poisson common factor model for modelling mortality of both genders jointly. Several alternatives are specified and applied to datasets from five developed regions. We find that direct parameterisation of cohort effect could improve model fitting, reduce the need for additional period factors, and produce consistent mortality forecasts for females and males. Furthermore, we find that the cohort effect appears to be gender indifferent for the populations examined and has an interaction effect with age in certain cases.